Does the Dumbbell-Carrying Position Change the Muscle Activity in Split Squats and Walking Lunges? - Stastny, Petr; Lehnert, Michal; Zaatar, Amr M Z; Svoboda, Zdenek; Xaverova, Zuzana (Journal of strength and conditioning research, 2015)
The forward walking lunge (WL) and split squat (SSq) are similar exercises that have differences in the eccentric phase, and both can be performed in the ipsilateral or contralateral carrying conditions. This study aimed to determine the effects of dumbbell-carrying position on the kinematics and electromyographic (EMG) amplitudes of the gluteus medius (Gmed), vastus medialis (VM), vastus lateralis (VL), and biceps femoris during WLs and SSqs. The resistance-trained (RT) and the non-resistance-trained (NT) groups (both n = 14) performed ipsilateral WLs, contralateral WLs, ipsilateral SSqs, and contralateral SSqs in a randomized order in a simulated training session. The EMG amplitude, expressed as a percentage of the maximal voluntary isometric contraction (%MVIC), and the kinematics, expressed as the range of motion (ROM) of the hip and knee, were measured during 5 repetition maximum for both legs. The repeated measure analyses of variance showed significant differences between the RT and NT groups. The NT group showed a smaller knee flexion ROM (p < 0.001, η = 0.36) during both types of WLs, whereas the RT group showed a higher eccentric Gmed amplitude (p < 0.001, η = 0.46) during all exercises and a higher eccentric VL amplitude (p < 0.001, η = 0.63) during contralateral WLs. Further differences were found between contralateral and ipsilateral WLs in both the RT (p < 0.001, η = 0.69) and NT groups (p < 0.001, η = 0.80), and contralateral WLs resulted in higher eccentric Gmed amplitudes. Contralateral WLs highly activated the Gmed (90% MVIC); therefore, this exercise can increase the Gmed maximal strength. The ipsilateral loading condition did not increase the Gmed or VM activity in the RT or NT group.
Keywords: biomechanika; Muscle, Skeletal; lidé; Adult; Isometric Contraction; elektromyografie; Walking; odporový trénink; Resistance Training; Lower Extremity; chůze; Humans; průřezové studie; Cross-Sectional Studies; Electromyography; mužské pohlaví; mladý dospělý; Biomechanical Phenomena; dolní končetina; Young Adult; Male; kosterní svaly; dospělí; isometrická kontrakce